Pre-Existing Anti-Vector Immunity to Adenovirus-Inspired VLP Vaccines Shows an Adjuvant-Dependent Antagonism - Salomé Gallet; Dalil Hannani; Sebastian Dergan-Dylon; Emilie Vassal-Stermann; Isabelle Bally; Christopher Chevillard; Daphna Fenel; Olivier Epaulard; Pascal Poignard; Pascal Fender (Vaccines)
Background/Objectives: The use of virus-like particles (VLPs) in vaccinology has expanded significantly in recent years. VLPs have the advantage of being non-infectious while effectively stimulating B cell responses through the repetitive presentation of epitope motifs on their surface. Since VLPs are often derived from human-infecting viruses, preexisting immunity may influence the immune response they elicit, warranting further investigation. Methods: We have developed a 60-mer VLP derived from human adenovirus type 3, a common pathogen. We investigated the impact of pre-existing adenovirus immunity on the immunization outcome against the linear S14P5 epitope of SARS-CoV-2, which was engineered into the particle (Ad-VLP-S14P5). To this end, antibody responses to S14P5 were evaluated following immunization with Ad-VLP-S14P5 in either naive or vector-primed mice. Results: Mice with pre-existing anti-vector immunity exhibited significantly greater anti-S14P5 antibody responses compared to vector-naive animals, demonstrating a beneficial impact of prior anti-adenovirus responses. However, the addition of an oil-in-water adjuvant for the immunizations abolished this positive impact, even leading to a deleterious effect of the pre-existing anti-vector immunity. Conclusions: The data suggest that the immune status against immunizing VLPs must be taken into consideration when designing immunization protocols. Importantly, the effects of prior immunity may vary depending on the nature of the protocol, including factors such as adjuvant use.